Students’ Mathematical Reasoning in Learning Arithmetic Sequences through Contextual Teaching and Learning - Putri Azzahra; Yusuf Hartono (SJME (Supremum Journal of Mathematics Education), 2026)
This study aims to describe the mathematical reasoning abilities of tenth-grade students at SMA Pusri Palembang in learning arithmetic sequences after the implementation of the Contextual Teaching and Learning (CTL) model. The study was motivated by students’ difficulties in presenting mathematical statements, making conjectures, performing manipulations, and drawing logical conclusions. The CTL model was selected because it connects mathematical concepts with real-life contexts and encourages active student participation in the learning process. This research employed a qualitative descriptive method, with data collected through classroom observations, posttests, and interviews. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that students’ mathematical reasoning abilities varied across different levels. Students in the high category were able to fulfill most indicators of mathematical reasoning, those in the moderate category met some indicators, while students in the low category experienced difficulties in understanding arithmetic sequence concepts. The implementation of the CTL model through context-based student worksheets (LKPD) was shown to enhance student engagement and support systematic reasoning in problem-solving processes, despite challenges related to limited time and unequal student participation.